Desenvolvimento tecnológico de supositórios vaginais contendo nanopartículas poliméricas de tioconazol - Cossetin, Luciana Filippin (2015)
The development of nanostructured materials has provided better control of the release and targeting of active substances to the treatment site, minimizing adverse effects, in addition to contributing to increased therapeutic efficacy. In this sense, these carriers are an alternative for the development of products administered by vaginal route because the pharmaceutical forms commonly used promote inadequate distribution and penetration of drugs, in addition to the reduced time spent on site. Therefore, this study aimed to develop vaginal suppositories containing dried products prepared from polymeric nanoparticle suspensions containing tioconazole, an antifungal used to treat vulvovaginitis. Suspensions of polymeric nanospheres and nanocapsules containing tioconazole (3 mg / ml) were prepared and evaluated for average particle diameter (166-203 nm) polydispersion index (less than 0.20), negative zeta potential (6 - 10 mV), pH (weakly acidic), drug content (value close to the theoretical) and encapsulation efficiency (approximately 100%), which were adequate and stable over the period of 30 days. After the suspensions were subjected to spray drying to obtain the solid intermediates, which were characterized in relation to the weight yield of resuspending in water content profile of particle size distribution, drug content, humidity and morphology. Regarding these characteristics, the results were satisfactory: yield weight, approximately 60%, drug content close to the theoretical value (21 mg / g), resuspending ratio close to unity and maintenance of submicrometric particle size. These characteristics have remained after 30 days of storage at room temperature, only dried products containing the nanospheres. Subsequently, the dried products were incorporated into a gelatin-glycerin base to obtain vaginal suppositories. All formulations had surface characteristics and homogeneous dimensions; drug content close to the theoretical concentration (23 mg / suppository); average weight between 4.51 and 4.57 g; content uniformity and disintegration time less than 60 minutes. Suppositories consisting of the nanospheres enabled greater control of the release of tioconazole compared with suppositories containing the drug not associated. Thus, the formulations proposed in this work may constitute an alternative for the administration by vaginal route tioconazole, better acceptability compared to the existing dosage forms (creams, gels) enabling, by definition, a greater therapeutic effect of the drug in order the advantages that nanotechnology presents.